A nationwide pilot study on breast cancer screening in Peru - Araujo, Jhajaira M. (2023)
“Introduction: A high prevalence of advanced breast cancer (BC) is a common scenario in Latin America. In Peru, the frequency of BC at Stages III/IV is ≈50% despite implementation of a programme for breast cancer screening (BCS) along the country. We carried out a study to assess the feasibility and develop an instrument to evaluate the knowledge, barriers and perception about BCS in a nationwide pilot study in Peru among candidates for BCS. Methods: We conducted a systematic review of 2,558 reports indexed in PubMed, Scopus, Web of Science, Medline-Ovid and EMBASE, regarding to our study theme. In total, 111 were selected and a 51-items survey was developed (eight items about sociodemographic characteristics). Patients were recruited in public hospitals or private clinics, in rural and urban areas of nine departments of Peru. Results: We surveyed 488 women from: Lima (150), Cajamarca (93), Ica (59), Arequipa (56), Loreto (48), Ancash (38), Junín (15), Puerto Maldonado (15) and Huancavelica (14); 27.9% of them were from rural areas. The mean of age was 53.3 years (standard deviation ± 9.1). Regarding education level, 29.8% had primary, 33.2% secondary and 37.0% higher education. In total, 28.7% of women did not know the term ‘mammogram’ and 47.1% reported never receiving a BCS (36.9% from urban and 73.5% from rural population). In women that underwent BCS, only 67% knew it is for healthy women. In total, 54.1% of patients had low levels of knowledge about risk factors for BC (i.e. 87.5% of women respond that injuries in the breast produce cancer). Cultural, economic and geographic barriers were significantly associated with having a mammogram where 56.9% of participants considered a cost ≤ 7 USD as appropriate. Mammogram was perceived as too painful for 54.9% of women. In addition, women with a self-perception of low-risk for BC and a fatalistic perception of cancer were less likely to have a BCS. Conclusion: We found that it is feasible to conduct a large-scale study in Peru. The results of this pilot study highlight an urgent need of extensive education and awareness about BCS in Peru.“